КРАТКИЙ ОБЗОР ИСЛАМСКОГО СТРАХОВОГО ИНСТИТУТА (Journal of actual problems of jurisprudence, 2019)
In given article the author referring to the theoretical and practical data, shows features of Islamic insurance model. Also wasmade the comparative analysis of Islamic insurance institute with traditional insurance institute.